2021
DOI: 10.46827/ejhrms.v5i2.1108
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Work Motivation, Work Environment and Quality of Communication on Employee Performance at the Regional Secretariat of South Kalimantan Province, Indonesia

Abstract: Local government and government agencies therein have an important role in carrying out government functions and regional development. One of the agencies within the Regional Government is the Regional Secretariat of the South Kalimantan Province. Every government agency is required to be able to optimize the performance of its employees, as well as the factors that influence it, namely work motivation, work environment and quality of communication. The research objective was to determine 1) the effect of work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 0 publications
1
32
0
6
Order By: Relevance
“…Based on several definitions of performance, it can be determined that performance is the result of work achieved by an employee or worker in carrying out his or her functions given the assigned responsibilities. Maryani, Entang and Tukiran (2021) There are four indicators to measure performance (Alexandro, 2021), which include the following:…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Based on several definitions of performance, it can be determined that performance is the result of work achieved by an employee or worker in carrying out his or her functions given the assigned responsibilities. Maryani, Entang and Tukiran (2021) There are four indicators to measure performance (Alexandro, 2021), which include the following:…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Prior research found that the combination of work motivation and work discipline had a significant impact on the performance of employees at the Bogor City Regional Secretariat. The implementation is done by combining work incentive and work discipline to deliver higher performance improvement (Maryani et al, 2018). This study's findings provide a unique viewpoint on the workplace, considering the work environment and colleague relationships.…”
Section: Discussionmentioning
confidence: 96%
“…e) Independence, is the level of an employee who can carry out his work function and commitment. This is a level where employees have an obligation to work with agencies and employee responsibilities towards the organization (Maryani et al, 2021).…”
Section: Employee Performancementioning
confidence: 99%